Efektivitas Minum Seduhan Daun Mint (Mentha Piperita) terhadap Frekuensi Emesis Gravidarum pada Ibu Hamil Trimester I di Wilayah Kerja Puskesmas Harapan Raya Pekanbaru - Tri Fitri Angraini; Lisviarose Lisviarose; Wira Akdeni Aifa; Fatma Nadia (Pusat Riset dan Inovasi Nasional, 2026)
The 2021 Indonesia Demographic and Health Survey (IDHS) reported that 45% of pregnant women experienced emesis gravidarum, increasing to 58% in 2022. In Riau Province, the prevalence of emesis gravidarum is estimated at 58% and tends to rise annually. If not properly managed, emesis gravidarum may adversely affect both maternal and fetal health. One non-pharmacological management approach is the use of herbal remedies. This study aimed to determine the effectiveness of mint leaf infusion in reducing the frequency of emesis gravidarum among first-trimester pregnant women in the working area of Harapan Raya Public Health Center, Pekanbaru. This research employed a quantitative method with a quasi-experimental design using a two-group pretest–posttest approach. The sample consisted of 30 first-trimester pregnant women experiencing emesis gravidarum, including 15 respondents in the intervention group and 15 in the control group, selected through purposive sampling. Data were collected using the PUQE-24 questionnaire and analyzed using univariate and bivariate analyses. The Shapiro–Wilk test indicated that the data were not normally distributed; therefore, the Wilcoxon Signed-Rank Test was used for bivariate analysis. The results showed a significant reduction in the frequency of emesis gravidarum in the intervention group after the administration of mint leaf infusion, with a p-value of 0.317 (p < 0.05), whereas no significant change was observed in the control group. It can be concluded that mint leaf infusion is effective in reducing the frequency of emesis gravidarum among first-trimester pregnant women. Mint leaf infusion is recommended as a safe and easily applicable non-pharmacological therapy in antenatal care services.